PENINGKATAN POTENSI PARIWISATA MELALUI PENYUSUNAN KONSEP TATA ZONASI WILAYAH - Laurensia, A.B.; Melvin, E.; Paramadhyaksa, I.N.W.; Ananta, M.D.S.; Safira, R.; Ramadiyan, R.S. (Buletin Udayana Mengabdi; Vol 23 No 3 (2024): Buletin Udayana Mengabdi, 2023)
Kelan Traditional Village is one of the villages in Indonesia which has a high tourism appeal. Kelan Traditional Village is famous for its unique culture and traditions that are still strongly maintained by the local community and also for its beautiful nature. Therefore, efforts are needed to increase the tourism potential of the Kelan Traditional Village through the arrangement and development of appropriate tourism facilities. One of the development efforts being carried out is through zoning arrangements for the Kelan Traditional Village area in the Udayana University Thematic Community Service Program (KKN-T) period I in 2022-2023. The method used in the implementation of this activity is through the collection, assessment, and qualitative data processing. The results found are the zoning concept of the Kelan Traditional Village area. The zoning concept is structured as a long-term plan in the period from 2023 to 2063. Keywords: Kelan Traditional Village, Development, Concept, Zoning, Tourism.